Psychooncology´s Clinical Intervention in Mexico - Escudero-Castelan, Ana Yareli; Galindo-Vázquez, Oscar (Mexican Journal of Medical Research ICSA, 2021)
Introduction: Cancer is a public health problem in Mexico, epidemiologically speaking and for biopsychosocially affecting those who suffer. In order to address this problem, in the medical area technological advances have allowed the management of the disease, while psycho-oncology has studied the psychosocial aspects present in the process of said condition and proposes problems that support the adaptation to the condition, decrease of psychopathological symptoms and an adequate quality of life. Objective: To analyze the characteristics of the clinical interventions made in Mexico in ​​psychooncology´s area in patients with active medical treatment. Material and Method: A review of the literature in the PubMed, Redalyc and Science Direct databases was carried out with the keywords "Psychooncology" and "Mexico". Studies were identified in which a psycho-oncological intervention was performed in Mexico and its characteristics was analyzed using the “PICO” strategy. Results: Three articles were selected that fulfill the inclusion criteria, 66.6% were randomized controlled clinical studies and 33.3% quasi-experimental, 66.6% of the interventions performed were cognitive-behavioral and 100% positive results in their variables evaluated. Conclusion: The information available in Mexico reflects the existing problem in descriptive studies of psychosocial variables related to cancer, however, it is still scarce in relation to psycho-oncological interventions, however, the evidence found demonstrates its problem in variables of anxiety, quality of life, body image and distress.